The relationship between job satisfaction and organizational commitment among uniformed personnel in the public sector: a case study at the Malaysia Royal Customs Department of Port Klang, Selangor / Azian Manap - Manap, Azian (2003)
Organizational Commitment and job satisfaction may determine the successful and the failure of the organization, which mean the organization, can sustain their performance when it have a dedicated, competitive workforce and the quality of its commitment. Therefore, this study are examine the relationship between job satisfaction and organizational commitment among uniformed personnel in the public sector. A case study at the Malaysia Royal Customs of Port Klang Selangor. A sample of 60 uniformed staffs in Malaysia Royal Customs Department was interviewed. The study is try to find the relationship between job satisfaction and organizational commitment with the demographic factors (age, gender, status, education, salary, job tenure and race), work itself, pay, promotion, supervision and co-workers. Instead of interviews and self-administered questionnaires other method of research that have been used in this study like data collection, cluster sampling technique, also statistical package for social sciences (SPSS). The findings hopefully can contribute and help the Malaysia Royal Customs Department in enhance the level of job satisfaction and organizational commitment.